Self‐Healing in Supramolecular Polymers - Campanella, Antonella; Döhler, Diana; Binder, Wolfgang H. (Macromolecular rapid communications., 2018)
Adaption and self‐healing are two major principles in material science, often coupled with the placement of supramolecular moieties within a material. Proper molecular design can enable self‐healing within such materials, displaying enormous potential in technology and application. Here, basic physicochemical aspects as well as new material developments in the field are described, published after a recent review in Macromolecular Rapid Communications in 2013. What makes a supramolecular material self‐healing? This article provides insight into this complex question, discussing the dynamics of supramolecular entities within a material, together with newly reported work in the field since 2013.